Genome-Wide DArTSeq Genotyping and Phenotypic Based Assessment of Within and Among Accessions Diversity and Effective Sample Size in the Diverse Sorghum, Pearl Millet, and Pigeonpea Landraces - Allan, Victor; Vetriventhan, Mani; Senthil, Ramachandran; Geetha, S.; Deshpande, Santosh; Rathore, Abhishek; Kumar, Vinod; Singh, Prabhat; Reddymalla, Surender; Azevedo, Vânia C. R. (Frontiers in Plant Science, 2020)
Germplasm should be conserved in such a way that the genetic integrity of a given accession is maintained. In most genebanks’, landraces constitute a major portion of collections, wherein the extent of genetic diversity within and among landraces of crops, vary depending on the extent of outcrossing and selection intensity infused by farmers. In this study, we assessed the level of diversity within and among 108 diverse landraces and wild accessions using both phenotypic and genotypic characterization. This includes 36 accessions in each of sorghum, pearl millet, and pigeonpea, conserved at ICRISAT genebank. We genotyped about 15 to 25 individuals within each accession, totaling 1980 individuals using the DArTSeq approach. This resulted in 45,249, 19,052, and 8211 high-quality single nucleotide polymorphism (SNPs) in pearl millet, sorghum, and pigeonpea, respectively. Sorghum had then lowest average phenotypic (0.090) and genotypic (0.135) within accession distances, while pearl millet had the highest average phenotypic (0.227) and genotypic (0.245) distances. Pigeonpea had an average of 0.203 phenotypic and 0.168 genotypic within accession distances. Analysis of molecular variance also confirms the lowest variability within accessions of sorghum (26.2%) and the highest of 80.2% in pearl millet, while an intermediate in pigeonpea (57.0%). The effective sample size required to capture maximum variability and to retain rare alleles while regeneration ranged from 47 to 101 for sorghum, 155 to 203 for pearl millet, and 77 to 89 for pigeonpea accessions. This study will support genebank curators in understanding the dynamics of population within and among accessions and devising appropriate germplasm conservation strategies, and aid in their utilization for crop improvement.